Supply Chain Optimization Model for Fresh Cow's Milk to Reduce Carbon Emissions and Food Waste: Model Optimasi Rantai Pasok Susu Sapi Segar untuk Mereduksi Emisi Karbon dan Food Waste - Jeremi, Nofariza Aulia; Vanany, Iwan (Universitas Muhammadiyah Sidoarjo, 2023)
The food and beverage industry occupies an important position in Indonesia, with growth in 5 (five) years, an average of 8.16%. In 2022, the food and beverage industry contributed more than one-third or 37.77% of the GDP of the non-oil and gas processing industry. However, growth considered positive for the economy is actually a threat to the environment. With the high demand for food, food waste and carbon emissions from all food supply chain (FSC) activities increase. This study raises a case of a dairy product processing supply chain in the West Java region with multiple milk suppliers (KUD Susu), a single processing production plant, multi distributors, and multi-consumer retail with multi-echelon, multi-period, and multi-product friendly conditions. Environment by considering food waste and carbon emissions as a function of the objective model. In solving this problem, the Mixed Integer Linear Programming (MILP) model is used in modeling supply chain processes to optimize total cost/TC, total food waste/TFW, and total carbon emissions/TCE. The results of the completion of the research showed a total cost of IDR 18,036,770,000, a total food waste/TFW of 21,734 liters, and a total carbon emission/TCE of 109,526 l.CO2-eq.